2019
DOI: 10.1111/cdev.13248
|View full text |Cite
|
Sign up to set email alerts
|

Are Socially Anxious Children Poor or Advanced Mindreaders?

Abstract: Why are some children more socially anxious than others? One theory holds that socially anxious children are poor mindreaders, which hampers their social interactions; another that socially anxious children are advanced mindreaders leading to heightened self‐consciousness in social situations. To test these theories simultaneously, this study (N = 105, ages 8–12) assessed children's mindreading (accuracy in detecting mental states from the eye region), self‐consciousness (indexed as physiological blushing duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
41
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(48 citation statements)
references
References 85 publications
(158 reference statements)
4
41
3
Order By: Relevance
“…Again, we found that blushing, indexed as the temperature increase, predicts the development of SAD symptoms at 7.5 years, even after controlling for earlier social anxiety symptoms and fearful temperament . We found the same result in children aged 8-12 (Nikolić, van der Storm, Colonnesi, Brummelman, Kan, & Bögels, 2019)-children with more SAD symptoms displayed higher increases in temperature during a performance in front of a small audience.…”
Section: Shynesssupporting
confidence: 77%
“…Again, we found that blushing, indexed as the temperature increase, predicts the development of SAD symptoms at 7.5 years, even after controlling for earlier social anxiety symptoms and fearful temperament . We found the same result in children aged 8-12 (Nikolić, van der Storm, Colonnesi, Brummelman, Kan, & Bögels, 2019)-children with more SAD symptoms displayed higher increases in temperature during a performance in front of a small audience.…”
Section: Shynesssupporting
confidence: 77%
“…It is important to acknowledge here that the work by Nikolić and colleagues () described above also reported a positive indirect association between adolescents' ability to read others' mental states from the eye region and self‐reported social anxiety, mediated by blushing. This finding is interesting as it suggests that better ability to read others' mental states may increase children's sensitivity to self‐related social cues, which in turn may enhance social anxiety.…”
Section: Introductionmentioning
confidence: 60%
“…In the present study we focused on the predictive role of ToM in typically developing children's social anxiety, a topic that has been overlooked in the past years. The few empirical studies on this issue are, however, promising as they suggest that higher performance on ToM tasks is associated with lower levels of social anxiety during the preschool (Colonnesi, Nikolić, de Vente, & Bögels, ) and the primary school (Banerjee & Henderson, ; Broeren & Muris, ; Nikolić et al, ) years. More specifically, Colonnesi and colleagues () found that children's performance on ToM tasks was associated concurrently and negatively with parents' reports on their children's social anxiety symptoms at 4.5 years.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations